(untitled) (Raparin Journal of Humanities (RJH), 2024)
The nations of the world have paid attention to preserve their musical heritage in many fields, including education system and teaching music, and have used their musical heritage in their educational music programs, including the method of playing the piano which is the main aim of this research. Some of music composers have used popular and famous songs as an educational approach to teach the piano. Therefore, the researcher has selected some examples of famous Kurdish songs and used them for the beginner level. "Using Kurdish Songs in the Piano Method" is the combination of Kurdish song heritage with a very important instrument of music, which has a very important and influential role in the art of music in general, in the process of music education in particular. In this regard, this study uses Kurdish song heritage as an educational model for piano playing at the beginning level for adults. Many studies confirm that pieces of music and exercises that use the melodies of traditional and popular songs are the best teaching materials for teaching music. It also helps music learners to know their music heritage and it can strengthen their cultural identity as well.